Development of an active cooling mechanism to increase the efficiency of photovoltaic module - Farhana Zainuddin (School of Electrical System Engineering, University Malaysia Perlis, 2013)
The objectives of this research are to study the suitability of solar irradiance for power generation in Perlis and analyse the influence of the temperature towards the efficiency of PV power conversion